The Challenges Faced by International Students in Learning English at Al-Madinah International School, Zliten, Libya - Ekhil, Fatima Mohammed; Al-Goal, Hala Salem; Al-Jmeil, Salma Ali; Salem, Mona M. M. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The international school helps international students learn English and improves their language level. This study aims to help the students improve their English language and face the difficulties that prevent them from learning it. However, it has been shown that the International School suffers from a lack of strategies and modern methods in teaching the English language. This research used qualitative and quantitative methods, and it included 12 students from grades five, six, seven, and eight, as well as four teachers in the International School. Therefore, the results have shown that the majority of the students and some teachers declare that the school lacks modern strategies for teaching the English language. The researchers recommended that the students should develop their language by themselves and also recommend that the school improve the educational process in all aspects of teaching by using modern strategies and methods.